Исследование взаимодействия алмаза с высоконеравновесными материалами на основе титана - Ашкинази, Е.Е.; Ральченко, В.Г.; Конов, В.И.; Заведеев, Е.В.; Басов, А.А.; Цыганков, П.А.; Мастюков, В.Н.; Гершман, И.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
Experiments on high-temperature annealing and friction behavior in a system “intermetallic Ti-Al and polycrystalline diamond films” have been carried out, that showed an effective catalytic interaction of the intermetallic alloys with diamond leading to diamond-graphite transition. A pilot batch of intermetallic alloys of Ti3Al TiAl and TiAl3 compositions used in the studies have been prepared specially for this project in Scientific Educational Center “Energomashinostroenie” of N. Bauman MGTU. To prevent an Al “burning off” effect in melting process that can disturb the alloy stoichiometry a special three-stage melting algorithm has been developed. Tribology parameters in the friction pair are evaluated. A rapid increase in friction power was observed under certain friction conditions, related to formation of submicron size particles between sliding surfaces, which are enriched with carbon transferred from the graphitized diamond surface. The contact interaction of CVD diamond with the alloys is interesting for mechanochemical synthesis on nanoscale powders such as metal-carbon particles. Abrading of diamond surface is revealed, assuming the potential use of this process for diamond polishing.